Pelatihan Usaha Produk Tanaman Obat Keluarga di Desa Duwet Krajan, Kabupaten Malang - Fadil Risdian Ansori; Amelya Qois Nabillah; Adinda Wahyu Widhi Astuti; Ranti Aisuka Rinjani; Mentari Dwi Prihatiningrum; Istiqlaliyah Muflikhati (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Coronavirus disease 2019 is a family of viruses that cause disease ranging from mild to serious illness, such as common cold and serious disease like MERS and SARS. Covid-19 pandemic has an impact on the economy, agriculture, and food. One of the economically affected is Duwet Krajan Village. Duwet Krajan has various potentials that can be continuously developed, one of which is agricultural potential in the form of toga. The aim of implementing training and counseling in Duwet Krajan Village is to provide education and understanding about improving the family economy in the midst of a pandemic. The method used is quantitative research and active participation. The activity was carried out from November to December 2020. The results obtained from training and counseling were the knowledge and skills of partners in the toga processing business.increased obtained from training and counseling are the increased knowledge and skills of partners in processing toga. This results that toga training and counseling had an impact on increasing the knowledge and skills of the PKK Dusun Duwet Krajan. Kata kunci: covid 19, pandemic, toga, training